2006
DOI: 10.1227/01.neu.0000194638.61073.fc
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Surgical Clipping of Unruptured Aneurysms as it Compares with a 10-Year Nonclipping Survival Period

Abstract: Studies on natural history of unruptured intracranial aneurysms suggest 10 year cumulative bleeding-related mortality and severe morbidity of no less than 7.5%. In our study, surgical clipping resulted in an 0.8% rate of mortality and 3.4% permanent morbidity. This suggests that surgical clipping has the potential of a superior outcome to the natural history of patients who have an estimated life expectancy of no less than 10 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(14 citation statements)
references
References 77 publications
1
12
1
Order By: Relevance
“…24 It has Our results showed that the pooled rates of morbidity as defined by mRS were 5% (95% CI  1-10%) and 8% (95% CI  3-14%) for coiling and clipping, respectively, which is consistent with previous studies where the rates of morbidity was reported to be 1% for endovascular coiling and 3% for surgical clipping. 29,30 These findings indicate that the two procedures bear similar risks of morbidity, which is further supported by our results that the pooled risk ratios of morbidity as defined by mRS was 0.53 (95% CI  0.18-1.52). Moreover, our results showed that the risk ratio of morbidity assessed through GOS was 0.67 (95% CI  0.18-2.45).…”
Section: Discussionsupporting
confidence: 81%
“…24 It has Our results showed that the pooled rates of morbidity as defined by mRS were 5% (95% CI  1-10%) and 8% (95% CI  3-14%) for coiling and clipping, respectively, which is consistent with previous studies where the rates of morbidity was reported to be 1% for endovascular coiling and 3% for surgical clipping. 29,30 These findings indicate that the two procedures bear similar risks of morbidity, which is further supported by our results that the pooled risk ratios of morbidity as defined by mRS was 0.53 (95% CI  0.18-1.52). Moreover, our results showed that the risk ratio of morbidity assessed through GOS was 0.67 (95% CI  0.18-2.45).…”
Section: Discussionsupporting
confidence: 81%
“…Park et al describe a direct endovascular mortality rate of 7.6% in ruptured aneurysms [25], while Zheng et al report a mortality rate of 0.85% [26]. A direct mortality rate of 0.8% was stated for the microsurgical clipping procedure in the treatment of non-ruptured aneurysms [27]. De Vries et al found a combined procedural persistent neurological morbidity and mortality after endovascular treatment and open surgical clipping of 2.1% and 1.4%, respectively [28].…”
Section: Discussionmentioning
confidence: 99%
“…This figure is significantly greater than the 4.2% combined morbidity and mortality rates that their patient population actually experienced, suggesting that surgical treatment may represent a superior approach to conservative management in patients with life expectancies greater than 10 years [31]. …”
Section: Treatment Options For Uiasmentioning
confidence: 99%